Tantangan dan Strategi Pengajaran Sastra dalam Pembelajaran Bahasa Indonesia Bagi Penutur Asing - Nanda Gultom (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2022)
This study aims to describe the challenges and strategies in learning literature for BIPA students. The dynamics of BIPA learning always encourage teachers to be adaptive in dealing with problems and problems in learning. This study uses a qualitative descriptive method which aims to identify challenges and strategies for teaching Indonesian literature for BIPA students. The research data came from literature studies and the results of observations and interviews with BIPA teachers at the UPI and UNY language centers. Interviews were conducted with an interview instrument that had been adapted to the focus of the researcher's study. The results of this study are presented descriptively. Based on the results of this study, challenges in teaching literature for BIPA students are students' enthusiasm or interest in literature, selecting literary material according to students' needs, introduction to the culture contained in literary works, explaining the meaning of sentences using figures of speech or idioms, using literary language that is different from communicative language, understanding connotative meaning in literature. Based on these challenges, there are several strategies that can be applied to deal with them, namely, using appropriate methods such as discussion methods, direct methods, grammar translation methods, repetitive methods, discovery learning methods, scientific learning approaches, Problem Based Learning and sociodrama. Besides that, it is also necessary to use media to help students understand such as videos, pictures and puzzles. The use of comparative literature, transformation of literary works, analysis of student needs are also strategies that can be used as an alternative in studying literature for BIPA students.